Psychological, social factors, and smoking behavior mediated the effects of cannabis use on personality disorders: A Mendelian randomization study - Ni, Yao; Li, Juanmei; Tang, Zitian; Zhang, Youqian; Feng, Yanyan (Frontiers in Psychiatry, 2025)
BackgroundRapid changes in attitudes, legality, and patterns of cannabis use (CU) underscore the importance of understanding its impact on mental health. Although links between CU and personality disorders (PDs) are documented, their causality remains uncertain.MethodsEmploying Genome-Wide Association Studies (GWAS) data, this study investigated the causal relationship between cannabis use disorder (CUD) and lifetime cannabis use (LCU) with 9 types of PD risk through Mendelian randomization (MR) analysis. The primary method was the inverse variance weighted (IVW) method, supplemented by multivariable MR to assess direct effects independent of mental, social, and substance use factors, and mediation MR to explore mediating factors.ResultsCorrections for the false discovery rate revealed significant causal associations between CUD and an increased risk of emotionally unstable PD (EUPD; ORIVW = 1.228, 95% CI 1.069–1.411), overall PD (ORIVW = 1.186, 95% CI 1.065–1.321), and schizoid PD (SPD; ORIVW = 1.644, 95% CI 1.131–2.390). Mediation analysis identified schizophrenia (SCZ), major depressive disorder (MDD), neuroticism, and smoking initiation (SmkInit) as shared mediating factors between CUD and both EUPD and overall PD, with an additional mediating factor, household income (HI), specific to the CUD-to-overall PD pathway. In contrast, no mediating factors were found between CUD and SPD. Notably, a bidirectional causal relationship was observed between overall PD and CUD (ORIVW = 1.399, 95% CI 1.033–1.895). Suggestive evidence indicated a causal link between lifetime cannabis use (LCU) and overall PD risk (ORIVW = 1.074, 95% CI 1.008–1.146).ConclusionThis study offers new insights into the potential impact of CU on the development and progression of various PDs, laying the groundwork for targeted interventions to mitigate its effects on mental health.